Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Drought Reduces Formation, but Enhances Persistence, of Mineral‐Associated Organic Matter in a Grassland Soil - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Nicole DiDonato; Katerina Estera‐Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; William Kew; Ljiljana Paša‐Tolić; Eric Slessarev; Jennifer Pett‐Ridge (Global Change Biology, 2026)
Drought effects are pervasive in terrestrial ecosystems, yet there is limited understanding of how drought impacts the transformation of plant carbon (C) inputs to mineral‐associated organic matter (MAOM)—the largest and slowest‐cycling pool of soil organic carbon (SOC). In a 12‐week 13 C‐CO 2 greenhouse labeling experiment, we tracked the formation of MAOM derived from the two dominant sources of plant C input to the mineral soil—living root inputs ( 13 C‐rhizodeposits) and decaying root inputs ( 13 C‐root detritus)—under normal moisture and droughted conditions in a semiarid grassland soil. At the end of the 12‐week period, we also measured the persistence of 13 C‐MAOM formed from rhizodeposits versus root detritus via a subsequent persistence assay. Drought reduced the formation of MAOM derived from living roots by decreasing rhizodeposits, reducing microbial growth rates, and altering the composition of organic matter, lipids, and metabolites. Drought initially delayed the formation of MAOM derived from root detritus by slowing the early stages of root litter decomposition (week 4–8), but did not decrease total MAOM formation by the end of the 12‐week period. Notably, drought enhanced the persistence of MAOM derived from root detritus, but did not influence the persistence of MAOM derived from rhizodeposits. Our results provide some of the first direct evidence that drought can reduce the formation of MAOM in a grassland soil, but may enhance its persistence, based on the source of plant input from which MAOM is derived.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Migratory patterns and seasonal habitat use of great hammerhead sharks ( Sphyrna mokarran ) in the southeastern United States - Grace A. Casselberry; Gregory B. Skomal; Lucas P. Griffin; Jacob W. Brownscombe; John T. Finn; Joseph Dello Russo; Alex Filous; Peter E. Holder; Ben Daughtry; Jeff Kneebone; Danielle Morley; Susan K. Lowerre‐Barbieri; et al. (Journal of Fish Biology, 2025)
The great hammerhead shark ( Sphyrna mokarran ) is a highly mobile shark species whose population in the United States declined dramatically through the early 2000s. Their spatial ecology is poorly understood, creating challenges for effective conservation of this enigmatic marine predator. Using acoustic telemetry and network analyses, we describe the movement patterns of 15 mature great hammerhead sharks (207–331.5 cm fork length) primarily within the waters of the southeastern United States from April 2019 to December 2022, including identifying movement corridors, core use areas and seasonal shifts in habitat use. Great hammerheads exhibited partial migration; some sharks undertook consistent, repeatable, round‐trip migrations between the tagging site in the Florida Keys and northern points in the Gulf of Mexico and Atlantic coast. Conversely, others remained in the Florida Keys year‐round. Network analysis coupled with community detection algorithms revealed that individual great hammerheads displayed oceanic basin affinity, favouring migration to either the Atlantic Ocean or Gulf of Mexico. Great hammerheads that remained in the Florida Keys shifted their habitat use seasonally from inshore channels (spring and summer) to offshore artificial reefs and the natural reef tract (summer through winter). These shifts may be driven by prey availability, as core use areas often corresponded to known locations of seasonal spawning aggregations for reef fish. These data fill an important knowledge gap for great hammerhead migratory patterns that can improve spatial management strategies for this historically overexploited species. We discuss the importance of drawing upon data from multiple tagging locations for highly mobile species management, particularly in the designation of essential fish habitat.

Metal contaminant risk at active floating photovoltaic sites and future research roadmap - Moreen Akomea-Ampeh; Eliot A. Atekwana; Elliott P. Steele; Alex E. Cagle; Alona Armstrong; Stephen J. Thackeray; Steven Sadro; Olusola O. Ololade; Olatubosun A. Fasipe; Rebecca R. Hernandez (Journal of Environmental Management, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Measuring river slope using spaceborne GNSS reflectometry: Methodology and first performance assessment - Yang Wang; Y. Jade Morton; J. Toby Minear; Alexa Putnam; Alex Conrad; Penina Axelrad; R. Steven Nerem; April Warnock; Christopher Ruf; Daniel Medeiros Moreira; Matthieu Talpe (Remote Sensing of Environment, 2025)

Effects and economic viability of earthworm meal (Eisenia andrei) and zeolite in diets for Nile tilapia (Oreochromis niloticus) fingerlings - Alex Steven Valencia Ortiz; Guilherme Melgaço Heluy; Maria do Carmo Mohaupt Marques Ludke; Luis Otávio Brito; Juliana Ferreira dos Santos; Carlos Bôa-Viagem Rabello; Jorge Vitor Ludke; Adrielle Carneiro de Araújo Santos; Elton Francisco de Oliveira; José Anderson Gomes da Silva; Arlei Coldebella (Aquaculture International, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Synergistic polytherapy for the broad-spectrum treatment of chemically-induced seizures in rats - Alex S. Cornelissen; Roland M. van den Berg; Steven D. Klaassen; Jelle C. de Koning; Jan P. Langenberg; Elizabeth C.M. de Lange; Marloes J.A. Joosen (Toxicology and Applied Pharmacology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Geochemical analysis of bituminous samples from the Pre-Pottery Neolithic B site of Nahal Efe (Northern Negev, Israel): Earliest evidence in the region and an example of alteration of the Dead Sea bitumen - Jacques Connan; Ferran Borrell; Jacob Vardi; Samuel Wolff; Steven M. Ortiz; Michael Engel; Renaud Gley; Alex Zumberge (Organic Geochemistry, 2024)

Marine heatwaves redistribute pelagic fishing fleets - Nima Farchadi; Heather Welch; Camrin D. Braun; Andrew J. Allyn; Steven J. Bograd; Stephanie Brodie; Elliott L. Hazen; Alex Kerney; Nerea Lezama‐Ochoa; Katherine E. Mills; Dylan Pugh; Riley Young‐Morse; et al. (Fish and Fisheries, 2024)
Marine heatwaves (MHWs) have measurable impacts on marine ecosystems and reliant fisheries and associated communities. However, how MHWs translate to changes in fishing opportunities and the displacement of fishing fleets remains poorly understood. Using fishing vessel tracking data from the automatic identification system (AIS), we developed vessel distribution models for two pelagic fisheries targeting highly migratory species, the U.S. Atlantic longline and Pacific troll fleets, to understand how MHW properties (intensity, size, and duration) influence core fishing grounds and fleet displacement. For both fleets, MHW size had the largest influence on fishing ground area with northern fishing grounds gaining and southern fishing grounds decreasing in area. However, fleet displacement in response to MHWs varied between coasts, as the Atlantic longline fleet displaced farther in southern regions whereas the most northern and southern regions of the Pacific troll fleet shifted farther. Characterizing fishing fleet responses to these anomalous conditions can help identify regional vulnerabilities under future extreme events and aid in supporting climate‐readiness and resilience in pelagic fisheries.

The path from root input to mineral-associated soil carbon is dictated by habitat-specific microbial traits and soil moisture - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Amrita Bhattacharyya; Nicole DiDonato; Katerina Estera-Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; Jeffrey Kimbrel; Jose Liquet; Marissa Lafler; et al. (Soil Biology and Biochemistry, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Genetic sex determination improves Canadian Atlantic salmon ( Salmo salar ) population assessments - Martha J. Robertson; Sarah J. Lehnert; Nicholas I. Kelly; Lorraine C. Hamilton; Ross A. Jones; Alex L. Levy; Rebecca Poole; Chantelle M. Burke; Steven J. Duffy; Amber Messmer; Ian R. Bradbury (Fisheries Management and Ecology, 2024)
Estimating egg deposition for Atlantic salmon population assessments is made difficult by their lack of sexual dimorphism prior to the autumn spawning season. We quantified the effect of sex misclassification from subjective examination of external morphology on egg deposition estimates in four Atlantic salmon populations across multiple years. Sex classification of Canadian salmon using the genetic sex marker ( sd Y) was accurate (>97%), whereas sex classification based on subjective examination of external morphology was inaccurate, with misclassification rates dependent on sea age, life history, and sampling season. Sex misclassification led to annual egg deposition estimates that ranged from −36% to +56%. We found that sex could not be discriminated based on measures of external morphology.

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Individual variation and repeatability of Atlantic tarpon Megalops atlanticus migrations in the southern US: implications for conservation and management - Lucas P. Griffin; Jacob W. Brownscombe; Aaron J. Adams; JoEllen K. Wilson; Grace A. Casselberry; Peter E. Holder; Alex Filous; Susan K. Lowerre-Barbieri; Steven J. Cooke; Andy J. Danylchuk (Marine Biology, 2023)

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Classic Phytochemical Antioxidant and Lipoxygenase Inhibitor, Nordihydroguaiaretic Acid, Activates Phospholipase D through Oxidant Signaling and Tyrosine Phosphorylation Leading to Cytotoxicity in Lung Vascular Endothelial Cells - Narasimham L. Parinandi; Alex Liaugminas; Patrick J. Oliver; Saradhadevi Varadharaj; Anita Yenigalla; Austin C. Elliott; Sukruthi Arutla; Steven J. Campbell; Sainath R. Kotha; Shariq I. Sherwani; Vijay K. Kutala; Jodi C. McDaniel; et al. (Cell Biochemistry and Biophysics, 2023)

Active populations and growth of soil microorganisms are framed by mean annual precipitation in three California annual grasslands - Megan M. Foley; Steven J. Blazewicz; Karis J. McFarlane; Alex Greenlon; Michaela Hayer; Jeffrey A. Kimbrel; Benjamin J. Koch; Victoria L. Monsaint-Queeney; Keith Morrison; Ember Morrissey; Bruce A. Hungate; Jennifer Pett-Ridge (Soil Biology and Biochemistry, 2023)

Correction to: Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

A pilot study of cognition and creativity among persons with HIV disease referred for neuropsychological evaluation - Steven Paul Woods; Anastasia Matchanova; Christina Alex; Samina Rahman; Michelle A. Babicz; Kelli L. Sullivan; Gunes Avci; Rodrigo Hasbun; Pariya L. Fazeli; Thomas P. Giordano (Journal of NeuroVirology, 2022)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Higher white matter hyperintensity load adversely affects pre-post proximal cognitive training performance in healthy older adults - Emanuel M. Boutzoukas; Andrew O’Shea; Jessica N. Kraft; Cheshire Hardcastle; Nicole D. Evangelista; Hanna K. Hausman; Alejandro Albizu; Emily J. Van Etten; Pradyumna K. Bharadwaj; Samantha G. Smith; Hyun Song; Eric C. Porges; et al. (GeroScience, 2022)

PERFICT: A Re‐imagined foundation for predictive ecology - Eliot J. B. McIntire; Alex M. Chubaty; Steven G. Cumming; Dave Andison; Ceres Barros; Céline Boisvenue; Samuel Haché; Yong Luo; Tatiane Micheletti; Frances E. C. Stewart (Ecology Letters, 2022)
Making predictions from ecological models—and comparing them to data—offers a coherent approach to evaluate model quality, regardless of model complexity or modelling paradigm. To date, our ability to use predictions for developing, validating, updating, integrating and applying models across scientific disciplines while influencing management decisions, policies, and the public has been hampered by disparate perspectives on prediction and inadequately integrated approaches. We present an updated foundation for Predictive Ecology based on seven principles applied to ecological modelling: make frequent Predictions, Evaluate models, make models Reusable, Freely accessible and Interoperable, built within Continuous workflows that are routinely Tested (PERFICT). We outline some benefits of working with these principles: accelerating science; linking with data science; and improving science‐policy integration.

Yield Depression in New Zealand Potato Crops Associated with Soil Compaction and Soil-Borne Diseases - Sarah M. Sinton; Richard E. Falloon; Peter D. Jamieson; Esther D. Meenken; Farhat A. Shah; Hamish E. Brown; Steven J. Dellow; Alex J. Michel; John D. Fletcher (American Journal of Potato Research, 2022)
In New Zealand, potato crop yields of 90 t ha −1 are achievable but at 55 t ha −1 , the average is becoming economically unsustainable. In 2012/13, a grower-initiated survey found that Rhizoctonia solani and Spongospora subterranea (soil-borne pathogens) and soil compaction were widespread in 11 Canterbury potato crops. Targeted areas in these crops had measured yield losses of 0 (healthy plants) – 42 (diseased, resource constrained plants) t ha −1 , limiting the farmer-measured field yield to a 56 t ha −1 average. In 2014/15, growth, water use and health of three contrasting crops were measured. Near-potential yield was achieved in one crop when disease incidence and severity were low and resources adequate. The other two crops yielded less than potential; one had an inadequate water supply and the other widespread soil-borne disease. Any suspected links between soil-borne disease, soil compaction and yield were further investigated by using them as factors in replicated experiments reported elsewhere.

The SEEL motif and members of the MYB-related REVEILLE transcription factor family are important for the expression of LORELEI in the synergid cells of the Arabidopsis female gametophyte - Jennifer A. Noble; Alex Seddon; Sahra Uygun; Ashley Bright; Steven E. Smith; Shin-han Shiu; Ravishankar Palanivelu (Plant Reproduction, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The relation between falls risk and movement variability in Parkinson’s disease - Steven Morrison; Jacquelyn Moxey; Nick Reilly; Daniel M. Russell; Karen M. Thomas; Alex A. Grunsfeld (Experimental Brain Research, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Fifty-year change in penguin abundance on Elephant Island, South Shetland Islands, Antarctica: results of the 2019–20 census - Noah Strycker; Alex Borowicz; Michael Wethington; Steven Forrest; Vikrant Shah; Yang Liu; Hanumant Singh; Heather J. Lynch (Polar Biology, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Framework for assessing vertebrate invasive species damage: the case of feral swine in the United States - Stephanie Shwiff; Alex Pelham; Steven Shwiff; William Haden-Chomphosy; Vienna R. Brown; Karina Ernst; Aaron Anderson (Biological Invasions, 2020)
The aim of this study is to provide a general overview of the economic impacts associated with vertebrate invasive species (VIS) in the United States and suggests a methodology for differentiating types of damage. We identify a general framework for categorizing VIS damage that separates this damage into three main categories: destruction, depredation, and disease. We then examine how this framework fits into current published estimates of damage and management costs. Economic impacts associated with feral swine damage and management are plentiful enough to warrant separate treatment from other VIS and are observed in all three categories. For all VIS examined in this study, damage estimates associated with destruction provide the most evaluations of VIS impacts, especially destruction of crops. Evaluations of the losses associated with depredation are largely absent from the literature. We find that while published studies have estimated substantial economic impact associated with VIS, the current state of the literature focusing on VIS frequently fails to address all of the categories of damage, is difficult to compare or replicate, and is unsuited for extrapolation to nation-wide estimates of damage.

Global human influence maps reveal clear opportunities in conserving Earth’s remaining intact terrestrial ecosystems - Jason Riggio; Jonathan E. M. Baillie; Steven Brumby; Erle Ellis; Christina M. Kennedy; James R. Oakleaf; Alex Tait; Therese Tepe; David M. Theobald; Oscar Venter; James E. M. Watson; Andrew P. Jacobson (Global Change Biology, 2020)
Leading up to the Convention on Biological Diversity Conference of the Parties 15, there is momentum around setting bold conservation targets. Yet, it remains unclear how much of Earth's land area remains without significant human influence and where this land is located. We compare four recent global maps of human influences across Earth's land, Anthromes, Global Human Modification, Human Footprint and Low Impact Areas, to answer these questions. Despite using various methodologies and data, these different spatial assessments independently estimate similar percentages of the Earth's terrestrial surface as having very low (20%–34%) and low (48%–56%) human influence. Three out of four spatial assessments agree on 46% of the non‐permanent ice‐ or snow‐covered land as having low human influence. However, much of the very low and low influence portions of the planet are comprised of cold (e.g., boreal forests, montane grasslands and tundra) or arid (e.g., deserts) landscapes. Only four biomes (boreal forests, deserts, temperate coniferous forests and tundra) have a majority of datasets agreeing that at least half of their area has very low human influence. More concerning, all datasets. These findings suggest that about half of Earth's terrestrial surface has relatively low human influence and offers opportunities for proactive conservation actions to retain the last intact ecosystems on the planet. However, though the relative abundance of ecosystem areas with low human influence varies widely by biome, conserving these last intact areas should be a high priority before they are completely lost.

Cropping History Affects Potato Yields in Canterbury, New Zealand - Sarah M. Sinton; Steven J. Dellow; Peter D. Jamieson; Richard E. Falloon; Farhat A. Shah; Esther D. Meenken; Kate K. Richards; Alex J. Michel; Craig S. Tregurtha; Jennifer M. Mcculloch (American Journal of Potato Research, 2020)

Landscape patterns in top‐down control of decomposition: omnivory disrupts a tropical detrital‐based trophic cascade - Troy N. Simon; Andrew J. Binderup; Alex S. Flecker; James F. Gilliam; Michael C. Marshall; Steven A. Thomas; Joseph Travis; David N. Reznick; Catherine M. Pringle (Ecology, 2019)
Detrital‐based trophic cascades are often considered weak or absent in tropical stream ecosystems because of the prevalence of omnivorous macroconsumers and the dearth of leaf‐shredding insects. In this study, we isolate top‐down effects of three macroconsumer species on detrital processing in headwater streams draining Trinidad's northern mountains. We separated effects of different macroconsumers by experimentally manipulating their temporal access to isolated benthic habitat over the diel cycle. We found no evidence that omnivorous macroconsumers, including a freshwater crab ( Eudaniela garmani ) and guppy ( Poecilia reticulata ), increased leaf decomposition via consumption. By contrast, above a waterfall excluding guppies, the insectivorous killifish, Anablepsoides hartii , reduced the biomass of the leaf‐shredding insect Phylloicus hansoni 4‐fold, which consequently reduced leaf decomposition rates 1.6‐fold. This detrital cascade did not occur below the barrier waterfall, where omnivorous guppies join the assemblage and reduce killifish densities; here killifish had no significant effects on Phylloicus or decomposition rates. These patterns of detrital processing were also observed in upstream–downstream comparisons in a landscape study across paired reaches of six streams. Above waterfalls, where killifish were present, but guppies absent, leaf decomposition rates and Phylloicus biomass were 2.5‐ and ~35‐fold lower, respectively, compared to measurements below waterfalls. Moreover, the strength of top‐down control by killifish is reflected by the 20‐ and 5‐fold reductions in variability (± SE ) surrounding mean Phylloicus biomass and leaf decomposition rates in upstream relative to downstream reaches where no top‐down control was detected. Findings show a clear, detrital‐based trophic cascade among killifish, a leaf‐shredding insect, and leaf decomposition rates. Results also show how omnivorous guppies disrupt this cascade by depressing killifish densities, thereby releasing invertebrate shredders from predation, and significantly increasing decomposition rates. Moreover, this combination of direct and indirect trophic interactions drives patterns in decomposition rates in stream networks at a landscape scale, resulting in significantly lower rates of decomposition above vs. below barrier waterfalls. Our findings reveal that omnivory can result in significant indirect effects on a key ecosystem process, illustrating the importance of these hidden trophic pathways in detrital‐based systems and suggesting that resource control in tropical systems may be even more complex than previously envisioned.

HER3-Targeted Affibodies with Optimized Formats Reduce Ovarian Cancer Progression in a Mouse Xenograft Model - John S. Schardt; Madeleine Noonan-Shueh; Jinan M. Oubaid; Alex Eli Pottash; Sonya C. Williams; Arif Hussain; Rena G. Lapidus; Stanley Lipkowitz; Steven M. Jay (The AAPS Journal, 2019)

Indices of Canada’s future climate for general and agricultural adaptation applications - Guilong Li; Xuebin Zhang; Alex J. Cannon; Trevor Murdock; Steven Sobie; Francis Zwiers; Kevin Anderson; Budong Qian (Climatic Change, 2018)

Human Primary Cell-Based Organotypic Microtissues for Modeling Small Intestinal Drug Absorption - Seyoum Ayehunie; Tim Landry; Zachary Stevens; Alex Armento; Patrick Hayden; Mitchell Klausner (Pharmaceutical Research, 2018)

Soil compartment is a major determinant of the impact of simulated rainfall on desert microbiota - Shazia N. Aslam; Alex J. Dumbrell; Jamal S. Sabir; Mohammed H. Z. Mutwakil; Mohammed M. N. Baeshen; Salah E. M. Abo‐Aba; Dave R. Clark; Steven A. Yates; Nabih A. Baeshen; Graham J. C. Underwood; Terry J. McGenity (Environmental Microbiology, 2016)
Summary Although desert soils support functionally important microbial communities that affect plant growth and influence many biogeochemical processes, the impact of future changes in precipitation patterns on the microbiota and their activities is largely unknown. We performed in‐situ experiments to investigate the effect of simulated rainfall on bacterial communities associated with the widespread perennial shrub, Rhazya stricta in Arabian desert soils. The bacterial community composition was distinct between three different soil compartments: surface biological crust, root‐attached, and the broader rhizosphere. Simulated rainfall had no significant effect on the overall bacterial community composition, but some population‐level responses were observed, especially in soil crusts where Betaproteobacteria, Sphingobacteria, and Bacilli became more abundant. Bacterial biomass in the nutrient‐rich crust increased three‐fold one week after watering, whereas it did not change in the rhizosphere, despite its much higher water retention. These findings indicate that between rainfall events, desert‐soil microbial communities enter into stasis, with limited species turnover, and reactivate rapidly and relatively uniformly when water becomes available. However, microbiota in the crust, which was relatively enriched in nutrients and organic matter, were primarily water‐limited, compared with the rhizosphere microbiota that were co‐limited by nutrients and water.

Estimating the prevalence of hematological malignancies and precursor conditions using data from Haematological Malignancy Research Network (HMRN) - Jinlei Li; Alex Smith; Simon Crouch; Steven Oliver; Eve Roman (Cancer Causes & Control, 2016)

Stability and Reproducibility Underscore Utility of RT-QuIC for Diagnosis of Creutzfeldt-Jakob Disease - Maria Cramm; Matthias Schmitz; André Karch; Eva Mitrova; Franziska Kuhn; Bjoern Schroeder; Alex Raeber; Daniela Varges; Yong-Sun Kim; Katsuya Satoh; Steven Collins; Inga Zerr (Molecular Neurobiology, 2016)
Real-time quaking-induced conversion (RT-QuIC) allows the amplification of miniscule amounts of scrapie prion protein (PrP Sc ). Recent studies applied the RT-QuIC methodology to cerebrospinal fluid (CSF) for diagnosing human prion diseases. However, to date, there has not been a formal multi-centre assessment of the reproducibility, validity and stability of RT-QuIC in this context, an indispensable step for establishment as a diagnostic test in clinical practice. In the present study, we analysed CSF from 110 prion disease patients and 400 control patients using the RT-QuIC method under various conditions. In addition, “blinded” ring trials between different participating sites were performed to estimate reproducibility. Using the previously established cut-off of 10,000 relative fluorescence units (rfu), we obtained a sensitivity of 85 % and a specificity of 99 %. The multi-centre inter-laboratory reproducibility of RT-QuIC revealed a Fleiss’ kappa value of 0.83 (95 % CI: 0.40–1.00) indicating an almost perfect agreement. Moreover, we investigated the impact of short-term CSF storage at different temperatures, long-term storage, repeated freezing and thawing cycles and the contamination of CSF with blood on the RT-QuIC seeding response. Our data indicated that the PrP Sc seed in CSF is stable to any type of storage condition but sensitive to contaminations with blood (>1250 erythrocytes/μL), which results in a false negative RT-QuIC response. Fresh blood-contaminated samples (3 days) can be rescued by removal of erythrocytes. The present study underlines the reproducibility and high stability of RT-QuIC across various CSF storage conditions with a remarkable sensitivity and specificity, suggesting RT-QuIC as an innovative and robust diagnostic method.

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

11-trifluoromethyl-phenyldiazirinyl neurosteroid analogues: potent general anesthetics and photolabeling reagents for GABAA receptors - Zi-Wei Chen; Cunde Wang; Kathiresan Krishnan; Brad D. Manion; Randy Hastings; John Bracamontes; Amanda Taylor; Megan M. Eaton; Charles F. Zorumski; Joseph H. Steinbach; Gustav Akk; Steven Mennerick; et al. (Psychopharmacology, 2014)

How do various maize crop models vary in their responses to climate change factors? - Simona Bassu; Nadine Brisson; Jean‐Louis Durand; Kenneth Boote; Jon Lizaso; James W. Jones; Cynthia Rosenzweig; Alex C. Ruane; Myriam Adam; Christian Baron; Bruno Basso; Christian Biernath; et al. (Global Change Biology, 2014)
Potential consequences of climate change on crop production can be studied using mechanistic crop simulation models. While a broad variety of maize simulation models exist, it is not known whether different models diverge on grain yield responses to changes in climatic factors, or whether they agree in their general trends related to phenology, growth, and yield. With the goal of analyzing the sensitivity of simulated yields to changes in temperature and atmospheric carbon dioxide concentrations [ CO 2 ], we present the largest maize crop model intercomparison to date, including 23 different models. These models were evaluated for four locations representing a wide range of maize production conditions in the world: Lusignan (France), Ames ( USA ), Rio Verde (Brazil) and Morogoro (Tanzania). While individual models differed considerably in absolute yield simulation at the four sites, an ensemble of a minimum number of models was able to simulate absolute yields accurately at the four sites even with low data for calibration, thus suggesting that using an ensemble of models has merit. Temperature increase had strong negative influence on modeled yield response of roughly −0.5 Mg ha −1 per °C. Doubling [ CO 2 ] from 360 to 720 μmol mol −1 increased grain yield by 7.5% on average across models and the sites. That would therefore make temperature the main factor altering maize yields at the end of this century. Furthermore, there was a large uncertainty in the yield response to [ CO 2 ] among models. Model responses to temperature and [ CO 2 ] did not differ whether models were simulated with low calibration information or, simulated with high level of calibration information.

Niche divergence by deep‐sea octocorals in the genus Callogorgia across the continental slope of the Gulf of Mexico - Andrea M. Quattrini; Samuel E. Georgian; Luke Byrnes; Alex Stevens; Rosalia Falco; Erik E. Cordes (Molecular Ecology, 2013)
Environmental variables that are correlated with depth have been suggested to be among the major forces underlying speciation in the deep sea. This study incorporated phylogenetics and ecological niche models ( ENM ) to examine whether congeneric species of Callogorgia (Octocorallia: Primnoidae) occupy different ecological niches across the continental slope of the Gulf of Mexico (GoM) and whether this niche divergence could be important in the evolution of these closely related species. Callogorgia americana americana, Callogorgia americana delta and Callogorgia gracilis were documented at 13 sites in the GoM (250–1000 m) from specimen collections and extensive video observations. On a first order, these species were separated by depth, with C. gracilis occurring at the shallowest sites, C. a. americana at mid‐depths and C. a. delta at the deepest sites. Callogorgia a. delta was associated with areas of increased seep activity, whereas C. gracilis and C. a. americana were associated with narrow, yet warmer, temperature ranges and did not occur near cold seeps. ENM background and identity tests revealed little to no overlap in ecological niches between species. Temporal calibration of the phylogeny revealed the formation of the Isthmus of Panama was a vicariance event that may explain some of the patterns of speciation within this genus. These results elucidate the potential mechanisms for speciation in the deep sea, emphasizing both bathymetric speciation and vicariance events in the evolution of a genus across multiple regions.

Diel movements of out-migrating Chinook salmon (Oncorhynchus tshawytscha) and steelhead trout (Oncorhynchus mykiss) smolts in the Sacramento/San Joaquin watershed - Eric D. Chapman; Alex R. Hearn; Cyril J. Michel; Arnold J. Ammann; Steven T. Lindley; Michael J. Thomas; Philip T. Sandstrom; Gabriel P. Singer; Matthew L. Peterson; R. Bruce MacFarlane; A. Peter Klimley (Environmental Biology of Fishes, 2013)

Quantifying northward movement rates of eastern king prawns along eastern Australia - Matias Braccini; Michael F. O’Neill; Anthony J. Courtney; George M. Leigh; Alex B. Campbell; Steven S. Montgomery; A. J. Prosser (Marine Biology, 2012)

Synthesis of peptidomimetics, δ- and $${ε}$$ -lactam tetrazoles - Steven Gunawan; Kristen Keck; Alex Laetsch; Christopher Hulme (Molecular Diversity, 2012)

Establishment of exotic parasitoids of the coffee berry borer Hypothenemus hampei (Coleoptera: Curculionidae: Scolytinae) in Colombia through farmer participatory research - Luis F. Aristizábal; Hugo M. Salazar; Carlos G. Mejía; Mauricio Jiménez; Alex E. Bustillo; Steven P. Arthurs (International Journal of Tropical Insect Science, 2012)

Modelled and measured concentrations of peroxy radicals and nitrate radical in the U.S. Gulf Coast region during TexAQS 2006 - Roberto Sommariva; Tim S. Bates; Daniel Bon; Daniel M. Brookes; Joost A. de Gouw; Jessica B. Gilman; Scott C. Herndon; William C. Kuster; Brian M. Lerner; Paul S. Monks; Hans D. Osthoff; Alex E. Parker; et al. (Journal of Atmospheric Chemistry, 2011)

Comparison of Methods for Chemical Conjugation of an Influenza Peptide to Wild-Type and Cysteine-Mutant Virus-Like Particles Expressed in Pseudomonas fluorescens - Greg T. Cantin; Sol Resnick; Hongfan Jin; Ryan O’Hanlon; Octavio Espinosa; Alex Stevens; Jason Payne; Nicole R. Glenn; Lada Rasochova; Jeffrey R. Allen (International Journal of Peptide Research and Therapeutics, 2011)

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Genetic diversity and genomic distribution of homologs encoding NBS-LRR disease resistance proteins in sunflower - Osman Radwan; Sonali Gandhi; Adam Heesacker; Brett Whitaker; Chris Taylor; Alex Plocik; Richard Kesseli; Alexander Kozik; Richard W. Michelmore; Steven J. Knapp (Molecular Genetics and Genomics, 2008)

Are clownfish groups composed of close relatives? An analysis of microsatellite DNA variation in Amphiprion percula - PETER M. BUSTON; STEVEN M. BOGDANOWICZ; ALEX WONG; RICHARD G. HARRISON (Molecular Ecology, 2007)
A central question of evolutionary ecology is: why do animals live in groups? Answering this question requires that the costs and benefits of group living are measured from the perspective of each individual in the group. This, in turn, requires that the group's genetic structure is elucidated, because genetic relatedness can modulate the individuals’ costs and benefits. The clown anemonefish, Amphiprion percula , lives in groups composed of a breeding pair and zero to four nonbreeders. Both breeders and nonbreeders stand to gain by associating with relatives: breeders might prefer to tolerate nonbreeders that are relatives because there is little chance that relatives will survive to breed elsewhere; nonbreeders might prefer to associate with breeders that are relatives because of the potential to accrue indirect genetic benefits by enhancing anemone and, consequently, breeder fitness. Given the potential benefits of associating with relatives, we use microsatellite loci to investigate whether or not individuals within groups of A. percula are related. We develop seven polymorphic microsatellite loci, with a number of alleles (range 2–24) and an observed level of heterozygosity (mean = 0.5936) sufficient to assess fine‐scale genetic structure. The mean coefficient of relatedness among group members is 0.00 ± 0.10 ( n = 9 groups), and there are no surprising patterns in the distribution of pairwise relatedness. We conclude that A. percula live in groups of unrelated individuals. This study lays the foundation for further investigations of behavioural, population and community ecology of anemonefishes which are emerging as model systems for evolutionary ecology in the marine environment.

Winter survival of age-0 smallmouth bass, Micropterus dolomieu, in north eastern lakes - R. Allen Curry; Steve L. Currie; Steven K. Arndt; Alex T. Bielak (Environmental Biology of Fishes, 2005)

Formulation Development and Antitumor Activity of a Filter-Sterilizable Emulsion of Paclitaxel - Panayiotis P. Constantinides; Karel J. Lambert; Alex K. Tustian; Brian Schneider; Salima Lalji; Wenwen Ma; Bryan Wentzel; Dean Kessler; Dilip Worah; Steven C. Quay (Pharmaceutical Research, 2000)

Identification of potential inter-domain disulfides in three higher plant mitochondrial citrate synthases: Paradoxical differences in redox-sensitivity as compared with the animal enzyme - Fred J. Stevens; Alex Dong Li; S. Salman Lateef; Louise E. Anderson (Photosynthesis Research, 1997)

Chlamydomonas reinhardtii NADP-linked glyceraldehyde-3-phosphate dehydrogenase contains the cysteine residues identified as potentially domain-locking in the higher plant enzyme and is light activated - Alex Dong Li; Fred J. Stevens; Heather C. Huppe; Ralf Kersanach; Louise E. Anderson (Photosynthesis Research, 1997)